Osservazione dei fenomeni deformativi nel centro di Roma. Dall'applicazione di tecniche avanzate DInSAR, all'analisi qualitativa della natura del rumore dei dati COSMO Sky-Med - Morigi, Massimo (Archeomatica, 2015)
This work was created to focus the attention on a particular aspect of the equivocation (aliasing) of the measurements made with Differential SAR interferometry (DInSAR) X-band for the presence of snow. Such equivocation emerge after a careful interpretation of the results obtained through the application of techniques Advanced DInSAR (A-DInSAR) for the observation of the deformation phenomena of the monumental structures in the center of Rome. The qualitative analysis have enabled the identification of the appropriate tools of analysis. The work was developed through the employment of various tools of software SARPROZ and is part of a PhD in Geoinformation for the University of Tor Vergata.